Synthesis and characterization of poly(higher-alpha-olefin)s with a nickel(alpha-diimine)/methylaluminoxane catalyst system: effect of chain running on the polymer properties - Subramanyam, Ummadisetty; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2007)
Homopolymerization of octadecene-1 at different reaction conditions has been studied. Significant chain running can be seen at higher polymerization temperatures. Interestingly, insertion of octadecene-1 into a sterically hindered nickel-cation/carbon (secondary) bond is observed. The microstructure of the polymer was established using NMR spectroscopy. The effects of chain running on polymer melting, crystallization behavior, and dynamic mechanical thermal properties were studied using DSC and DMTA. The extent of chain running (i.e., 2 omega-, 1,omega-enchainments) decreases with an increase in the carbon number of alpha-olefins. (c) 2006 Wiley Periodicals, Inc.
Keywords: chain running; Crystallization; glass transition; melt transition; nickel (alpha-diimine); NMR; poly(alpha-olefin)s

Studies on the effect of glass transition on the crystalline transition in syndiotactic polystyrene - solvent complexes - Naidu, Sudhakar; Ramesh, N. C. (Macromolecular Symposia, 2008)
Amorphous syndiotactic polystyrene (sPS) was crystallized at room temperature in Norbornadiene (bicyclo[2,2,1]-hepta-2,5-diene), Mesitylene (1,3,5-Trimethyl benzene), 3-Carene (3,7,7-trimethyl bicyclo[4,1,0]hept-3-ene) and DMN (1,4-Dimethylnaphthalene) to form the sPS-solvent complex (h form) with respective solvent molecules. In situ HTFTIR studies showed that the delta form to gamma form transformation temperature occurs well below the glass transition temperature of sPS, which is depressed due to the presence of solvent in the amorphous phase; higher the solvent content in the complex, lower the transition temperature. Glass transition temperatures determined by Modulated differential scanning calorimetry (MDSC) coincide with the transition temperatures, indicating that the delta form transforms into gamma form at the glass transition temperature for these complexes. Such a behavior is very different from the behaviour of the sPS- solvent complexes formed by dichloromethane, chloroform, toluene, o-dichlorobenzene, decalin (cis-trans) etc. and for these complexes the transition occur well above the T(g).
Keywords: Crystallization; glass transition; infrared spectroscopy; Syndiotactic polystyrene

Ionic conductivity probed in main chain liquid crystalline azobenzene polyesters - Nardele, Chinmay G.; Dhavale, Vishal M.; Sreekumar, K.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2015)
Three main chain thermotropic liquid crystalline (LC) azobenzene polymers were synthesized using the azobenzene twin molecule (P4P) having the structure Phenylazobenzene-tetraethyleneglycol-Phenylazobenzene as the AA monomer and diols like diethylene glycol, tetraethylene glycol (TEG), and hexaethylene glycol as the BB comonomer. Terminal C(O)OMe units on P4P facilitated transesterification with diols to form polyesters. All polymers exhibited stable smectic mesophases. One of the polymers, Poly(P4PTEG) was chosen to prepare composite polymer electrolytes with LiCF3SO3 and ionic conductivity was measured by ac impedance spectroscopy. The polymer/0.3 Li salt complex exhibited a maximum ionic conductivity in the range of 10(-5) S cm(-1) at room temperature (25 degrees C), which increased to 10(-4) S cm(-1) above 65 degrees C. The temperature dependence of ionic conductivity was compared with the phase transitions occurring in the sample and it was observed that the glass transition had a higher influence on the ionic conductivity compared to the ordered LC phase. Reversible ionic conductivity switching was observed upon irradiation of the polymer/0.3 Li salt complex with alternate UV and visible irradiation. (c) 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 629-641
Keywords: azo polymers; glass transition; liquid-crystalline polymers (LCP)

Toughening of epoxy novolac resin using cardanol based flexibilizers - Gour, Rajeshwari S.; Kodgire, Vivek V.; Badiger, Manohar V. (Journal of Applied Polymer Science, 2016)
In this work, two different cardanol based epoxies (Cardolite NC-514 and Cardanol NC-547) were employed as flexibilizers to toughen an epoxy novolac resin namely, poly[(phenylglycidyl ether)-co-formaldehyde] (PPGEF). 4,4-Diamino-3,3-dimethyl dicyclohexyl methane (BMCHA) was used as a curing agent. Differential scanning calorimetry and dynamic mechanical thermal analysis of the composites showed a gradual decrease in glass transition temperatures (T-g) with increase in cardolite content confirming the incorporation of flexible moieties into the brittle resin matrix. Improvement in toughening of PPGEF/Cardolite composites was manifested by increase in the izod impact strength of both the composites. The tensile strength increased marginally for composites with increasing amount of Cardolite NC-514 but decreased for the composites containing Cardolite NC-547. This was attributed to the lack of rotational motion in the chain due to close proximity of rigid phenyl rings in NC-547. SEM of the cryo-fractured surfaces of composites showed good compatibility between PPGEF and cardanol based flexibilizers. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43318.
Keywords: composites; crosslinking; glass transition